Effect of Biofertilisers on Yield and Quality of Sweet Pepper (Capsicum annuum cv. grossum L.) - SAHOO, D; SAHOO, N R; PARAMJITA, D (Journal of the Indian Society of Coastal Agricultural Research, 2017)
The effects of biofertilizers along with organic and inorganic fertilizers were studied on growth, yield and quality of capsicum grown in sandy loam soils for two consecutive years 2011-2012 and 2012-13 at the Experimental Farm of Orissa University of Agriculture and Technology, Bhawanipatna. In the pooled analysis, the treatments with application of chemical fertilizers (RDF) along with basal application of vermicompost showed better yield performance than with RDF and basal application of farm yard manure. Supplementing nutrients through 100% chemical fertilizers i.e. RDF were significantly inferior in producing fruit yield to organic manures (vermicompost and farm yard manure) applied with chemical fertilizers (RDF). Also, it is seen that basal application of organic manures showed significant difference in yield than the split application as top dressing. Application of 75% nitrogen and phosphorus, full potassium along with biofertilizers (Azotobacter + Azospirillum + PSB) and FYM (10 t ha-1) showed the best result with respect to growth i.e. plant height (57.68 cm), number of leaves (109.43), number of branches (10.48), leaf area (104.70 cm2) per plant, days to 50% flowering (39.63 days), yield (45.76 t ha-1), TSS (6.37Â° Brix) of fruits, ascorbic acid content in fruit (172.53 mg 100 g-1) and chlorophyll content in fruit (4.89 mg g-1) and is significantly different from all other treatments tried in the experiment. As regards the net return is concerned, maximum return of Rs. 139005 per hectare was obtained where the crop was supplied with 75% nitrogen, phosphorus and 100% potassium of the recommended dose of chemical fertilizer in presence of farm yard manure along with bioinoculants. The highest benefit: cost recorded was 2.55 (mean of two years) which was significantly superior to other treatments.